La relación entre las funciones ejecutivas y comunicación pragmática en la población autista - Narciso Cabrel, Lucía Marleny (2024)
Autistic individuals present notable socio-communicational difficulties when engaging in and maintaining a conversation, perceiving others' intentions, expressing their emotions and desires, which are part of pragmatic communication. There are variables that could explain these social pragmatic difficulties, one of them being executive functions. This applied review seeks to examine the relationship between executive functions and pragmatic communication in autistic individuals through the review of previous studies. This applied search was conducted following the PRISMA guidelines (Bonfill & Urrutia, 2013) in the Scopus, Web of Science, and Scielo databases. Considering the inclusion and exclusion criteria, ten articles were selected that measured executive functions and pragmatic communication in the autistic population. It was found that there is a positive and statistically significant relationship between pragmatic communication and executive functions. It is concluded that executive functions explain some social and communicational deficits in the autistic community. Additionally, this relationship is mediated by variables of self-management and socialization.